The case study handbook how to read, discuss, and write persuasively about cases - Ellet, William (Harvard Business School Press, 2007)
Provides an approach for analyzing, discussing, and writing about cases. This book shows how to classify cases according to analytical task they require (solving a problem, making a decision, or forming an evaluation) and establish a base of knowledge about a case. It shows how to talk about cases in class.